Drawing the Beasts: Animal Depiction on Caucasian Bronze Belts - Castelluccia, Manuel (Actual Problems of Theory and History of Art, 2024)
Before the influence of Greek art in the Hellenistic period, peoples of the Caucasus region mostly expressed their art and beliefs by focusing on animal depictions. During the Early and Middle Bronze Ages, representations of animals appeared especially on objects of precious metals, such as jewelry or silver goblets. Their style showed foreign influences from Mesopotamia. Towards the end of the 2nd millennium B.C., the Caucasus region witnessed remarkable transformations, encompassing all human-related spheres: landscape, settlement patterns, material culture, and art. One of the most distinctive features of this period is a dramatic increase in metalwork production. Several metal objects have incised decorations, whereas others are made of animal shapes. The largest category of objects with artistic representation is bronze belts, and thin metal plaques, primarily found in graves. The artistic repertoire is vast, with a strong focus on representations of real animals of the surrounding landscapes. They are realized according to a local style, where Mesopotamian, Anatolian, or Iranian influences are practically absent. This paper aims to offer a deeper insight into the animal representations on bronze belts and to track the possible symbolic significance of its figures and compositions. It focuses on specific features of the representation, the scenes, the imagery, and highlights influences and connections with other cultural and historical contexts of the Caucasus and neighboring regions.